Economic assessment of a community-based care package for people with lower limb disorder caused by lymphatic filariasis, podoconiosis and leprosy in Ethiopia. (9th November 2020) - Hounsome, Natalia; Kinfe, Mersha; Semrau, Maya; Ali, Oumer; Tesfaye, Abraham; Mengiste, Asrat; Bremner, Stephen; Ahmed, Abdulkadir; Fekadu, Abebaw; Davey, Gail
Abstract: We conducted an implementation research study to integrate a holistic package of physical health, mental health and psychosocial care for podoconiosis, lymphatic filariasis and leprosy into routine healthcare in Gusha cluster, Guagusa Shikudad district, northwest Ethiopia. The healthcare package included training patients in lower limb hygiene and skin care and provision of shoes, hygiene supplies and medication. The implementation activities included training events, workshops, awareness raising, self-help groups, supportive supervision, staff secondments and advisory board meetings. The cost of implementing the care package in Gusha cluster, with a population of 30 558 people, was 802 655 Ethiopian birr (ETB) (£48 159) and the cost of delivering care to 235 participants was 204 388 ETB (£12 263), or 870 ETB (£52) per person. There was a 35% decrease in the mean disability scores (measured using the World Health Organization Disability Assessment Schedule 2.0) and a 45% improvement in the dermatology-specific quality of life (measured using the Dermatology Life Quality Index) at the 3-month follow-up compared with baseline. There were reductions in the number of days with symptoms, days off usual activities/work and days with reduced activity due to illness, all of which were statistically significant. Our pilot suggests that integration of the care package into routine healthcare in Ethiopia may be effective in improving health-related quality of life and disability and reducing time out of economic activity due to illness.